Better the devil you know: exposing the data sharing practices of smartphone apps - Van Kleek, M; Liccardi, I; Binns, R; Zhao, J; Weitzner, D; Shadbolt, N (Association for Computing Machinery, 2017)
Most users of smartphone apps remain unaware of what data about them is being collected, by whom, and how these data are being used. In this mixed methods investigation, we examine the question of whether revealing key data collection practices of smartphone apps may help people make more informed privacy- related decisions. To investigate this question, we designed and prototyped a new class of privacy indicators, called Data Con- troller Indicators (DCIs), that expose previously hidden informa- tion flows out of the apps. Our lab study of DCIs suggests that such indicators do support people in making more confident and consistent choices, informed by a more diverse range of factors, including the number and nature of third-party companies that access users’ data. Furthermore, personalised DCIs, which are contextualised against the other apps an individual already uses, enable them to reason effectively about the differential impacts on their overall information exposure.